Hubungan Perilaku Ibu Dalam Pencegahan Diare Dengan Kejadian Diare Pada Batita 1-3 Tahun Di RS MITRA MEDIKA Medan - yuniati yuniati (Program Studi Ilmu Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Indonesia Timur, 2021)
Diarrhea is a change in the consistency of bowel movements that occur suddenly from being dense to more watery and the number of child defecation is more than 3 times a day. WHO data (2017) states, nearly 1.7 billion cases of diarrhea occur in children with the mortality rate is around 525,000 in children under five each year. This study aims to determine the relationship between maternal behavior in preventing diarrhea and the incidence of diarrhea in toddlers 1-3 years at Mitra Medika Hospital in 2020. This study used an analytic survey with a cross-sectional approach, using the chi-square test and continuity correction test. The populations were 100 respondents who have toddlers 1-3 years. The sample was 50 respondents. The type of data used primary data. The data analysis used univariate and bivariate analysis. The results showed that there was a relationship between maternal knowledge in preventing diarrhea and the incidence of diarrhea (p-value= .017), there was a relationship between maternal attitudes in preventing diarrhea and the incidence of diarrhea (p-value=.012), there was a relationship between maternal actions in preventing diarrhea and the incidence of diarrhea. Diarrhea (p-value = .006). The conclusion of this study is that there is a relationship between maternal behaviors in preventing diarrhea with the incidence of diarrhea in toddlers 1-3 years at Mitra Medika Hospital Medan in 2020. It is hoped that toddlers will increase their knowledge, attitudes and actions towards preventing diarrhea in toddlers.